2017
DOI: 10.1007/s13760-017-0762-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuron-specific enolase levels as a marker for possible neuronal damage in idiopathic intracranial hypertension

Abstract: Although formerly considered as a "benign" disease, the presence of some important problems such as vision loss, resistance to appropriate medical treatment and relapses suggests that neuronal damage might play a role in the pathophysiology of IIH. In order to demonstrate possible neuronal damage/dysfunction participating in IIH pathophysiology, we aimed to investigate the relationship between serum neuron-specific enolase (NSE) levels and clinical features in patients with idiopathic intracranial hypertension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
0
12
1
Order By: Relevance
“…In a previous study, Samanc et al reported that there was no correlation between BMI and NSE. 25 The difference between their findings and the findings in the present study might be partly ascribed to differences in sample size. In addition, the mean age of people enrolled in this study was 50.49±13.52 years, while in the study by Samanc et al , the mean ages of idiopathic intracranial hypertension and control groups were 35.40±9.85 and 37.10±9.65 years, respectively.…”
Section: Discussioncontrasting
confidence: 87%
“…In a previous study, Samanc et al reported that there was no correlation between BMI and NSE. 25 The difference between their findings and the findings in the present study might be partly ascribed to differences in sample size. In addition, the mean age of people enrolled in this study was 50.49±13.52 years, while in the study by Samanc et al , the mean ages of idiopathic intracranial hypertension and control groups were 35.40±9.85 and 37.10±9.65 years, respectively.…”
Section: Discussioncontrasting
confidence: 87%
“…[ [25][26][27][28] NSE and S100B are considered as biomarkers of glial cell damage or neuronal damage in patients with stroke or injury of the CNS. [29][30][31][32][33][34][35][36][37] Increased blood concentrations of NSE and/or S100B occur after hypoxia, hemorrhage, and injury to the CNS and always indicate that the BBB has been damaged. [38,39] We obtained a positive correlation between the presence of NSE and a worse neurological status on the first day, and between S100B and a poor status on the first and 30th day of stroke, which is consistent with the observations reported by other authors.…”
Section: Discussionmentioning
confidence: 99%
“…However, as the permanent damage of the optic nerve may not only depend on the severity of the papilledema but also on its duration, biomarkers indicating permanent optic nerve damage and the need for immediate surgical intervention are required. So far, few potential biomarkers have been evaluated (19,20). However, no biomarkers with diagnostic, prognostic or predictive value have been established for routine use.…”
Section: Introductionmentioning
confidence: 99%